Rejecting new technology: the case of genetically modified wheat - Berwald, Derek; Carter, Colin A.; Gruère, Guillaume P. P. (Wiley, 2006)
Canada has stringent regulations covering the release of new wheat varieties, but the United States has virtually no regulations in this area. Monsanto Co. developed genetically modified (GM) spring wheat for North America, and made a commitment to the U.S. industry to release this new technology simultaneously in both Canada and the United States, or not at all. The Canadian regulatory bias against new varieties acted as a veto against GM wheat and caused Monsanto to shelve the technology in both countries in 2004. Substantial economic rents were foregone in North America due to the rejection of this new technology.